God’s Alterity and the Particularity of Christ - Björn Vikström; Elli Barsnes (Svensk Teologisk Kvartalskrift)
The article explores ways of doing theology in a postmodern intellectual landscape. The authors claim that this requires a balance between the particularity of the Christ event and the universality of the mystery of God, which by necessity transgresses the limitations of individual perspectives. Relying upon the philosopher of religion Olli-Pekka Vainio, the authors propose that the crucial question in postmodern theology is what kind of particularism or fideism is applied, and whether the chosen position leaves room for discussions with outsiders or not. The article provides a comparison between how the philosopher Richard Kearney, of Roman-Catholic origin, and the Orthodox theologian David Bentley Hart relate the particularity of the Christ event to the unfathomability of God. They both underscore that Christians can learn from other religious traditions, and that other faiths or traditions have the potentiality to clarify aspects of the Christian tradition. Kearney's kenotic approach underscores God's unfathomability, while Hart's eschatological perspective gives the Christian story primacy as the central object of faith. The interchange between these two prominent thinkers contributes to the search for a way of doing theology that succeeds in combining a critical fidelity to the own tradition with a constructive dialogue with representatives of other traditions.